Possibility to use quanadex (dexmedetomidine) for caesarean section in patients with pre-eclampsia (Pain medicine, 2022)
A prospective, doubleblind, randomized, controlled clinical trial was conducted at the Republican Specialized Scientific and Practical Medical Center of Obstetrics and Gynecology of the Ministry of Health of the Republic of Uzbekistan. The inclusion criteria for pregnant women in the study was preeclampsia. All women were divided into 2 groups. In group I, premedication was performed on the table with sibazon 5 mg. In group II, starting from the moment of premedication, 0.5 µg/kg of quanadex (Yuriya Pharm) was administered intravenously for 15 minutes. The maintaining dose was 0.5–0.8 µg/kg/h. 0.5 % hyperbaric longocaine heavy was administered intrathecally at the LII–LIV level. Hemodynamics was assessed by echocardiography. BAC and electrolytes, lactate, glucose, hematocrit were studied on a gas analyzer “BGA102” Wondfo (Rain Sen Da), NTproBNP, CystatinC, interleukin6 and protein S100 were determined on an immunofluorescence analyzer Finecare™ FIA MeterPlus/FS 113 (Wonfo), sedation was assessed using the Richmond scale. Newborns were assessed for Apgar scores in the 1st and 5th minutes.The data obtained showed that patients randomized to the group with dexmedetomidine (Group II) were almost always better able to awaken than patients in the group with sibazon, and were distinguished by better hemodynamic stability, antinociceptive protection for surgical and anesthetic intervention, without pronounced arterial hypotension and bradycardia. It did not cause significant adverse outcomes in newborns.
Keywords: preeclampsia; dexmedetomidine; caesarean section